MLRU mapping - A concept of composite mapping unit for integrated land survey - Abichandani, C T; Sen, Amal Kumar (Annals of Arid Zone, 2016)
Working out of a composite mapping unit for integrated regional survey. with the aim of providing a basis for the assessment of the resource potentials of an area deserves special cartographic attention. The hitherto available mapping techniques do not fully serve the purpose under Indian arid zone conditions. A new composite mapping unit-Major Land Resources Unit (MLRU)-has been evolved based on the principle of classification of lands having recurring patterns of biotic and abiotic environments. The cartographic techniques and advantages of the MLRU system have been described.